Synthesis of one-dimensional van der Waals material alloys - Oh, Seungbae; Jeon, Jiho; Choi, Kyung Hwan; Chae, Sudong; Park, Jae Hyuk; Lee, Jae Hyun; Yu, Hak Ki; Choi, Jae Young (Applied Physics Letters, 2022)
For the van der Waals bond-based one-dimensional two- (Nb2Se9 and V2Se9) and three-component group (Ta2Ni3Se8, Ta2Pt3Se8, and Nb2Pd3Se8) materials, alloy phases were synthesized according to the mixing ratio of transition metals, and basic analysis of phase stability and lattice structure was performed. The formation of alloy phases corresponding to Nb2-xVxSe9 and Ta2MxN3-xSe8 (M, N = Ni, Pd, and Pt) was confirmed, and lattice engineering was possible by changing the interplanar distance according to the transition metal mixing ratio. Through elemental analysis of the synthesized material, it was also confirmed that the composition is close to the mixing ratio used for actual synthesis. In the future, the basic physical properties of the alloys will be evaluated and applied to various application devices.
Keywords: Alloy phasis; Lattice engineering; Lattice structures; Mixing ratios; One-dimensional; Stability structures; Synthesised; Three-component; Van der Waal; Van der Waal bonds